Habitat use and nursery evaluation for the longnose stingray Hypanus guttatus (Bloch & Schneider, 1801) using vertebral microchemistry. Issue 5 (4th August 2021) - Feitosa, Leonardo M.; Queiroz, Aristóteles P.N.; Labonne, Maylis; Dressler, Valderi L.; Lessa, Rosangela P.
ABSTRACT: Here, we use vertebral microchemistry to investigate the habitat use patterns of the longnose stingray Hypanus guttatus in the northern and northeastern regions of Brazil, and to evaluate the existence of potential nurseries of the species. Samples were collected in Maranhão, Rio Grande do Norte and Pernambuco states between 2008 and 2019. Trace element concentrations of Ba:Ca, Mg:Ca, Mn:Ca and Sr:Ca in vertebrae were determined through laser ablation inductively coupled plasma mass spectrometry. We used one‐step permutational ANOVAs to evaluate multi and single‐element differences in element:Ca ratios among life stages and sexes across and within sites. Element signatures differed among all sites for both single and multi‐element settings. However, there were few differences among life stages within sites, except for Mn:Ca between life stages for Maranhão state, and between sexes for Sr:Ca for both Pernambuco and Rio Grande do Norte, and Ba:Ca for Rio Grande do Norte. Furthermore, all multi and single‐element analyses across locations were significant and highlight the strong differences by sites. We also performed a nonmetric multidimensional scaling analysis, which demonstrated the strong differences for samples from Rio Grande do Norte and the other two sites. By analysing the lifetime transects of each sample, we observed that there was little variation in all element:Ca ratios within sites. Therefore, we argue that the longnose stingray likely does not display extensive habitat use shifts and fulfils much of its life cycle within each area. Finally, we obtained no evidence of nurseries for any site and suggest this is likely a pattern across the species distribution. Future studies investigating habitat use with samples from larger specimens (disc width > 90 cm, >15 years) are needed to better understand the species habitat use patterns across all size ranges.